Warming reinforces nonconsumptive predator effects on prey growth, physiology, and body stoichiometry. Issue 12 (1st December 2015) - Janssens, Lizanne; Van Dievel, Marie; Stoks, Robby
Abstract : While nonconsumptive effects of predators may strongly affect prey populations, little is known how future warming will modulate these effects. Such information would be especially relevant with regard to prey physiology and resulting changes in prey stoichiometry. We investigated in Enallagma cyathigerum damselfly larvae the effects of a 4°C warming (20°C vs. 24°C) and predation risk on growth rate, physiology and body stoichiometry, for the first time including all key mechanisms suggested by the general stress paradigm (GSP) on how stressors shape changes in body stoichiometry. Growth rate and energy storage were higher at 24°C. Based on thermodynamic principles and the growth rate hypothesis, we could demonstrate predictable reductions in body C:P under warming and link these to the increase in P‐rich RNA; the associated warming‐induced decrease in C:N may be explained by the increased synthesis of N‐rich proteins. Yet, under predation risk, growth rate instead decreased with warming and the warming‐induced decreases in C:N and C:P disappeared. As predicted by the GSP, larvae increased body C:N and C:P at 24°C under predation risk. Notably, we did not detect the assumed GSP‐mechanisms driving these changes: despite an increased metabolic rate there was neither an increase of C‐rich biomolecules (instead fat and sugar contents decreased under predation risk), nor a decrease of N‐rich proteins. We hypothesize that the higher C:N and N:P under predation risk are caused by a higher investment in morphological defense. This may also explain the stronger predator‐induced increase in C:N under warming. The expected higher C:P under predation risk was only present under warming and matched the observed growth reduction and associated reduction in P‐rich RNA. Our integrated mechanistic approach unraveled novel pathways of how warming and predation risk shape body stoichiometry. Key findings that (1) warming effects on elemental stoichiometry were predictable and only present in the absence of predation risk and that (2) warming reinforced the predator‐induced effects on C:N:P, are pivotal in understanding how nonconsumptive predator effects under global warming will shape prey populations.